Characterization of free volume during vulcanization of styrene butadiene rubber by means of positron annihilation lifetime spectroscopy and dynamic mechanical test - Marzocca, A.J. (2002)
An experimental investigation was performed to study the effect on the free volume of the advance of the cross-linking reaction in a copolymer of styrene butadiene rubber by sulfur vulcanization. The dynamic modulus and loss tangent were evaluated over samples cured for different times at 433 K by dynamic mechanical tests over a range of frequencies between 5 and 80 Hz at temperatures between 200 and 300 K. Using the William-Landel-Ferry relationship, master curves were obtained at a reference temperature of 298 K and the coefficients [formula presented] and [formula presented] were evaluated. From these parameters the dependence of the free volume on the cure time is obtained. Positron annihilation lifetime spectroscopy was also used to estimate the size and number density of free volume sites in the material. The spectra were analyzed in terms of continuous distributions of free volume size. The results suggest an increase of the lower free volume size when cross linking takes place. Both techniques give similar results for the dependence of free volume on the time of cure of the polymer. © 2002 The American Physical Society.